Opportunities for the Development of the National Idea in the Education System (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discusses the place and development of the national idea in the education system. Ideological education is a process aimed at shaping the worldview of a person, social group, nation, society, arming them with ideological knowledge that represents specific goals.